Call for Action to a Pandemic: Perception, Attitude and Practice among Adults with Chronic Diseases towards COVID- 19 at South-East Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Public awareness is the mainstay to control an emerging pandemic. This study investigated the knowledge, attitudes and practices of COVID-19 among chronic disease patients during the pandemic. Materials and methods: A cross-sectional study was conducted from June-October 2021 at Chittagong Medical College Hospital, Southern Bangladesh. This study included 1537 chronic disease patients by convenient sampling using a pre-structured questionnaire. Multivariable logistic regression analyses were performed to identify factors associated with poor knowledge and practice towards COVID-19. The strength of the association between the dependent and independent variables was demonstrated by computing Odds Ratio (OR) with a 95% Confidence Interval (CI). Correlation between knowledge, attitude and practice scores were done by using Pearson correlation coefficient. p-value 55 years reported poor knowledge. Educational status of “can’t read and write”, unemployment, multi-morbidity (OR= 3.06, 1.40, 2.06 with 95% CI and OR=2.95, 2.19, 2.22 with 95% CI respectively) and low monthly family income (p =